Highly efficient photoninitiators based on 4H-pyranylidene derivatives for two-photon laser printing - Royo, Raquel; Mainik, Philipp; Benitez-Martin, Carlos; Andreu, Raquel; Blasco, Eva; Najera, Francisco; Villacampa, Belén (Advanced Materials Technologies, 2023)
A series of four donor-acceptor-donor derivatives bearing 4H-pyranylidene and 4-methylcyclohexan-1-one units as donor and acceptor groups respectively is designed, synthesized, and photophysically characterized. Both experimental and theoretical studies reveal good two-photon absorption (2PA) properties for these systems. Decoration of the exocyclic position of the 4H-pyranylidene moiety with a thiophene ring results in high 2PA cross-section values (σ2PA) ≈700 nm, and remarkably, in the region between 900 and 1000 nm. Furthermore, all chromophores are evaluated as photoinitiators (PIs) for two-photon-laser printing at 780 nm, showing superior performance compared to the commonly used commercially available PI, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. Among the studied PIs, the ones equipped with a thiophene unit at the exocyclic position of the 4H-pyranylidene moiety exhibit the highest efficiency, enabling fast printing using low laser powers with even lower concentrations of PI. Overall, this study shows the great potential of this new class of PIs for application in the field of 3D nanoprinting.
Gesehen am 15.07.2024